Studio Building at 104-116 Tremont Street, 1905 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of the Studio Building at (from left to right) 104-116 Tremont Street, between Bromfield Street to the north and Hamilton Street to the south. The facade of the Studio Building faces northeast toward the Granary Burial Ground. Several businesses are housed in the Studio Building. Signage, awnings and a large clock adorn the facade of the building. Merchandise is displayed in several storefront windows. Two men stand behind a horse-drawn wagon in front of the building. A small boy can be seen in the window of a tailor shop at the northwest corner of the building above the Almeda Company storefront. Copyprint 9 3/8 x 7 1/2, 9 5/8 x 7 3/4 overall Photographs